2015
DOI: 10.1109/jsen.2014.2359228
|View full text |Cite
|
Sign up to set email alerts
|

Design of Induction Magnetometer Receiving Sensor for Through-the-Earth Communications

Abstract: A narrowband, high sensitivity, and low-power consumption induction magnetometer (IM) receiving sensor is designed, built, and tested for through-the-Earth (TTE) communications in this paper. The optimization method is described mathematically and applied for building an IM (central frequency 3180 Hz and 3-dB bandwidth 200 Hz). In this paper, we move the resonant frequency of the coils to the central frequency and optimize the parameters of the IM to minimize the equivalent input magnetic noise level to 7 fT/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Numerical methods have been described for optimising air-core magnetometer designs 5 , 10 15 . These have the benefit of requiring fewer assumptions than analytic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical methods have been described for optimising air-core magnetometer designs 5 , 10 15 . These have the benefit of requiring fewer assumptions than analytic methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, firstly, the carrier frequency was set to 85 Hz for TEC using SLF, and the resonant frequency of the primary receiving SCM was tuned to this carrier frequency [9] by C p . Thus, on one hand, the primary-receiving SCM can be designed for the desired narrow bandwidth.…”
Section: Solution To the Scm Optimization Problemmentioning
confidence: 99%
“…In this study, contour maps [9,13] are adopted, and the results are shown in Figs. 5 and 6 for the primary receiving and reference SCM, respectively.…”
Section: Solution To the Scm Optimization Problemmentioning
confidence: 99%
See 2 more Smart Citations